Diet quality indices for research in low- and middle-income countries: a systematic review - Trijsburg, L.; Talsma, Elise F.; Vries, J.H.M. de; Kennedy, G.; Kuijsten, A.; Brouwer, Inge D. (Oxford University Press, 2019)
# Context